2012
DOI: 10.1136/jclinpath-2011-200377
|View full text |Cite
|
Sign up to set email alerts
|

Stromal keratin expression in phyllodes tumours of the breast: a comparison with other spindle cell breast lesions

Abstract: The use of keratins as an adjunctive immunohistochemical diagnostic tool in the differential work-up of spindle cell tumours of the breast has to be interpreted with caution especially on limited core biopsy material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…The majority of PTs are negative for CKs and p63. 25 In a recent study of 32 PTs, it was found that p63, p40, and CKs can be focally positive in 57%, 29% and 21%, respectively, of malignant PT but not in benign or borderline PT. 26 These results suggest that these markers alone should not be used to differentiate metaplastic (sarcomatoid) carcinoma from malignant PT on core biopsy.…”
Section: Malignant Ptmentioning
confidence: 95%
“…The majority of PTs are negative for CKs and p63. 25 In a recent study of 32 PTs, it was found that p63, p40, and CKs can be focally positive in 57%, 29% and 21%, respectively, of malignant PT but not in benign or borderline PT. 26 These results suggest that these markers alone should not be used to differentiate metaplastic (sarcomatoid) carcinoma from malignant PT on core biopsy.…”
Section: Malignant Ptmentioning
confidence: 95%
“…Cytokeratin expression per se in a spindle cell lesion does not exclude other diagnoses. A recent study found focal expression of some cytokeratins in phyllodes tumours,17 although this is rarely a diagnostic problem as most phyllodes tumours show the typical fibroepithelial architecture. Also some sarcomas, such as leiomyosarcoma, can express cytokeratins.…”
Section: Spindle Cell Lesionsmentioning
confidence: 99%
“…Contrary to other studies, they observed some expression of keratins MNF116, 34bE12, CK7, CK14, AE1/3, and Cam5.2 in the stromal cells of 11.9%, 22%, 28.4%, 1.8%, 8.3%, and 1.8% of PTs, respectively. 69 However, keratin positivity was focal and patchy and was found in only 1% to 5% of stromal cells in these cases, and the explanation for keratin expression is uncertain. In an earlier study, Dunne et al 70 applied a panel of keratins (AE1/AE3, 34bE12, CK5 and CK14, Cam5.2, CK7 and CK19, and EMA), of which all were negative in the stromal components of 26 PTs.…”
Section: Cytokeratinsmentioning
confidence: 99%
“…Chia and colleagues 69 investigated a larger cohort of PTs using a wide panel of commonly used keratins, including MNF116, 34bE12, CK7, CK14, Cam5.2, and AE1/3. Contrary to other studies, they observed some expression of keratins MNF116, 34bE12, CK7, CK14, AE1/3, and Cam5.2 in the stromal cells of 11.9%, 22%, 28.4%, 1.8%, 8.3%, and 1.8% of PTs, respectively.…”
Section: Cytokeratinsmentioning
confidence: 99%